[ORIGINS]_Constructing A Spatial Lexicon: A Catalyst For Finding Place_[Locatedness] - Semple, Callum (School of Architecture, Planning and Geomatics, 2023)
Architecture in space and time. It passes through eons, morphing and changing. But its purpose remains the same, to provide the basics of shelter, of containment. Vessels to sustain and grow, be that physically, psychologically, or metaphorically. Layering, palimpsests of time, collages of assemblage. This inquiry, a speculative body of work looks to create an architecture that moves, architecture as an embodiment of art through the mediums of the hand/eye which is alchemic by nature. It is a Lexicon that is shaped upon the beginnings of land, the epistemicide that has taken place and the locale where this all began, within the VOC's Company Gardens, Cape Town, Southern Africa. Ideas are underpinned through the eyes of semantics, of origins, and through philosophers that look to challenge place, who look to subvert the status quo. The aim is to provide a speculative look at what can be envisioned in locatedness. To be located is the fundamental aspect of our existence. This architecture will be speculative, the land within the Cape was not ‘tabula rasa' [terra nullius] which draws on the ‘empty land myth' of the colonial hegemony. But, instead it's a land that is imbued in meaning, multiple aspects of lives lived and lives living. Through the trauma of the past, and misrepresentation, the only way forward is to ask questions, and to listen. As the translator of this project, it's an architecture to ask questions, some may be answered in the process but ultimately this is not a conclusion, but hopefully something which looks to invite narrative and dialogue leading into the future. To take and lead people where they may not have been before. Ultimately, the works looks to use deconstructivist notions as an apparatus to reclaim space [origin] – locatedness – through the lens of an interpretation receptacle of the First Peoples, with an emphasis on language through experience, connection, and landscape. An archive juxtaposed in dialogue with the anti-archive.